A socio-ecological approach to the declining Catalan clam fisheries. (15th March 2018) - Baeta, Marc; Breton, Françoise; Ubach, Raquel; Ariza, Eduard
Abstract: The world demand for marine bivalves continuously increased from 1980 to 2014. Their fisheries landings in the Mediterranean Sea also increased, until they began to drop in the last decade. This trend was particularly intense in the western Mediterranean Sea, where landings dropped from 4046 t (1996) to 425 t (2012). Since then, they have never recovered. We examined the status of the main commercial clam species in Catalonia (NW Mediterranean) one of the main productive areas of the western Mediterranean Sea, and analyzed the social and ecological context of the different small scale clam fisheries as an example of the Mediterranean as a whole to detect the possible causes of this negative trend. Our results reveal the critical status of all clam fisheries along the entire coast, where most clam stocks are currently collapsed or close to collapse. This trend mirrors the evolution of bivalve fisheries in the western Mediterranean. Many management failures and factors inhibiting the sustainability of clam fisheries over time were detected ( i.e. the nearly absence of resource monitoring or control of rules enforcement; lack of conflict resolution mechanisms among fishermen and other coastal users; the incongruence between appropriation and provision regulations, and deficient nested enterprises), suggesting that inadequate and incongruent management is largely to blame for the precarious present situation. However, our results also suggest that undetermined additional factors ( e.g . pathologies, pollution, climate change etc.) have also affected what were already highly stressed populations. Highlights: While clam demand increase worldwide, their landings drop in the western Mediterranean Sea. Our results revealed the critical status of the main clam fisheries on the Catalan coast. Many management failures and factors inhibiting the sustainability of clam fisheries over time were detected. Our results suggest that an inadequate management has strongly contributed to the present situation. Management guidelines are proposed.